High-Resolution MRI Findings following Trigeminal Rhizotomy - Northcutt, B.G.; Seeburg, D.P.; Shin, J.; Aygun, N.; Herzka, D.A.; Theodros, D.; Goodwin, C.R.; Bettegowda, C.; Lim, M.; Blitz, A.M. (American journal of neuroradiology : AJNR, 2016)
Patients with trigeminal neuralgia often undergo trigeminal rhizotomy via radiofrequency thermocoagulation or glycerol injection for treatment of symptoms. To date, radiologic changes in patients with trigeminal neuralgia post-rhizotomy have not been described, to our knowledge. The aim of this study was to evaluate patients after trigeminal rhizotomy to characterize post-rhizotomy changes on 3D high-resolution MR imaging. A retrospective review of trigeminal neuralgia protocol studies was performed in 26 patients after rhizotomy compared with 54 treatment-naïve subjects with trigeminal neuralgia. Examinations were reviewed independently by 2 neuroradiologists blinded to the side of symptoms and treatment history. The symmetry of Meckel's cave on constructive interference in steady-state and the presence of contrast enhancement within the trigeminal nerves on volumetric interpolated breath-hold examination images were assessed subjectively. The signal intensity of Meckel's cave was measured on coronal noncontrast constructive interference in steady-state imaging on each side. Post-rhizotomy changes included subjective clumping of nerve roots and/or decreased constructive interference in steady-state signal intensity within Meckel's cave, which was identified in 17/26 (65%) patients after rhizotomy and 3/54 (6%) treatment-naïve patients ( < .001). Constructive interference in steady-state signal intensity within Meckel's cave was, on average, 13% lower on the side of the rhizotomy in patients posttreatment compared with a 1% difference in controls ( < .001). Small regions of temporal encephalomalacia were noted in 8/26 (31%) patients after rhizotomy and 0/54 (0%) treatment-naïve patients ( < .001). Post-trigeminal rhizotomy findings frequently include nerve clumping and decreased constructive interference in steady-state signal intensity in Meckel's cave. Small areas of temporal lobe encephalomalacia are encountered less frequently.